Ekolinguistik Kuliner Makanan Khas Batak Toba - Nurhasanah, Yuni (Multiverse: Open Multidisciplinary Journal, 2024)
This study aims to explore the ecolinguistics of Batak Toba traditional cuisine, focusing on the relationship between language, culture, and environment in the culinary traditions of the Batak Toba community. The primary research question is how language and culinary practices reflect and influence the ecological and cultural perspectives of the Batak Toba people. The research employs qualitative methods, including field observations, in-depth interviews with community leaders and culinary experts, and text analysis from various literary sources. The findings reveal that Batak Toba cuisine serves not only as a means of nutritional fulfillment but also as a medium for preserving cultural and environmental values. Traditional dishes such as arsik and saksang carry profound ecological symbolism and demonstrate a harmonious relationship between humans and nature. The study concludes that understanding the ecolinguistics of Batak Toba cuisine is crucial for cultural and environmental preservation and can serve as a model for ecolinguistic studies in other regional culinary contexts.